2008
DOI: 10.1103/physrevc.78.034915
|View full text |Cite|
|
Sign up to set email alerts
|

Conformal relativistic viscous hydrodynamics: Applications to RHIC results atsNN=200GeV

Abstract: A new set of equations for relativistic viscous hydrodynamics that captures both weak-coupling and strongcoupling physics to second order in gradients has been developed recently. We apply this framework to bulk physics at the Relativistic Heavy Ion Collider (RHIC), both for standard (Glauber-type) as well as for colorglass-condensate (CGC) initial conditions and show that the results do not depend strongly on the values for the second-order transport coefficients. Results for multiplicity, radial flow and ell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
366
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 709 publications
(394 citation statements)
references
References 103 publications
(196 reference statements)
27
366
1
Order By: Relevance
“…On the experimental side, the elliptic flow observable v 2 , which is sensitive to the value of η in units of entropy density s, is now corrected for non-medium-generated two-particle correlations [12]. The conclusion that η/s must be much smaller than unity has so far withstood these refinements of heavy-ion phenomenology [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the experimental side, the elliptic flow observable v 2 , which is sensitive to the value of η in units of entropy density s, is now corrected for non-medium-generated two-particle correlations [12]. The conclusion that η/s must be much smaller than unity has so far withstood these refinements of heavy-ion phenomenology [11].…”
Section: Introductionmentioning
confidence: 99%
“…This early agreement between ideal hydrodynamics and experiment has been refined in recent times. On the theory side, the dissipative effects of shear viscosity η have been included in full 3d hydrodynamics calculations [8,9,10] and the sensitivity to initial conditions quantitatively estimated [11] for the first time. On the experimental side, the elliptic flow observable v 2 , which is sensitive to the value of η in units of entropy density s, is now corrected for non-medium-generated two-particle correlations [12].…”
Section: Introductionmentioning
confidence: 99%
“…The study of these collisions at the Relativistic Heavy Ion Collider (RHIC) and at the Large Hadron Collider (LHC) has demonstrated that matter at temperatures above the crossover between hot hadronic matter and hotter QGP exhibits strong collective phenomena [1][2][3][4][5][6][7] which can be described successfully by hydrodynamic simulations of the rapid expansion and cooling of the initially lumpy droplets of matter produced in the collisions [8][9][10][11][12][13][14][15][16][17][18]. Such strong collectivity has also recently been observed in smaller colliding systems, including p-Pb, p-p or 3 He-Au [19][20][21][22][23][24][25][26][27][28][29], for which hydrodynamic simulations also seem to be successful [30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent example of such a universal property is the ratio of shear viscosity η over entropy density s [24] which is known to obey η/s = 1/4π for any strongly coupled theory with a two-derivative gravity dual and unbroken SO(3) rotational symmetry [22,[25][26][27][28][29][30][31][32]. Current estimates for the value of η/s in the QGP extracted from heavy ion collision data are indeed close to 1/4π [33][34][35][36][37][38][39].…”
Section: Jhep12(2016)091mentioning
confidence: 91%